Kinematic differences on mid-range basketball jump-shot between experienced and less-experienced collegiate player - Syaukani, Agam Akhmad; Yan, Li Chun (Jurnal Keolahragaan, 2019)
Jump shot in modern basketball is an effective scoring way to overcome pressure of the defender. Fundamental jump shot technique relies on experience and biomechanical analyses. The purpose of this analysis was to evaluate kinematic profile of basketball players based on their experience level during mid-range jump shot. Four experienced basketball players and four less-experienced basketball players participated in the experiment. Jump shot phase was classified into 3 categories: preparatory, action, and follow-through. Angular displacement and angular velocity were measured using three-dimension (3D) motion capture technology. One-way Anova analysis indicated significant differences on several kinematic parameters between groups. On preparatory phase, experienced subject produced larger magnitude for right-shoulder extension (-10.3±14.7Ëš) and produced smaller angular velocity for hips flexion (41.0±11.6Ëš/s). During the action phase, experienced subject produced larger magnitude for right-wrist flexion (-145.9±40.3Ëš), larger angular velocity for right-wrist flexion (-182.8±35.7Ëš/s), larger angular velocity for ankle plantar flexion (-159.5±27.3Ëš/s), and larger angular velocity for right-elbow extension (-149.6±33.3Ëš/s). The findings of this study indicated that improper mechanics of basketball jump shot existed in less-experienced players. To practice jump shot technique, preparatory phase and action phase should be the main emphasis for every coach when deals with less-experienced player.